2023
DOI: 10.1093/tas/txad032
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of corn-fermented protein as a dietary ingredient in extruded dog and cat diets

Abstract: Most pet foods utilize traditional ingredients like corn, wheat, and soy. These ingredients and other grains, such as distillers dried grains (DDG), have been used by the pet food industry. Corn fermented protein (CFP) is a nutrient dense enhancement on DDG but has not been evaluated in pet food. Therefore, it was the objective of this study to determine the effect of CFP in the production of extruded pet diets, and to determine the effect on nutrient utilization (digestibility) and stool consistency in dogs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 32 publications
1
8
1
Order By: Relevance
“…These findings were similar to those of Yamka et al (2003), who reported that an increase in dietary fiber resulted in decreased digestion and greater fecal mass due to an increased rate of passage through the digestive system and decreased absorption. Previous studies have also reported increased fecal output in dogs consuming CFP compared with those consuming SBM, due to an increase in dietary fiber (Kilburn-Kappeler and Smith and Aldrich, 2023). However, in the current study, the fecal output of dogs fed CFP was comparable to that of those dogs fed CON and/or BDY, whereas a higher fecal output was observed for those dogs fed the BDY+DDGS treatment.…”
Section: Food Intake and Fecal Characteristicscontrasting
confidence: 83%
See 1 more Smart Citation
“…These findings were similar to those of Yamka et al (2003), who reported that an increase in dietary fiber resulted in decreased digestion and greater fecal mass due to an increased rate of passage through the digestive system and decreased absorption. Previous studies have also reported increased fecal output in dogs consuming CFP compared with those consuming SBM, due to an increase in dietary fiber (Kilburn-Kappeler and Smith and Aldrich, 2023). However, in the current study, the fecal output of dogs fed CFP was comparable to that of those dogs fed CON and/or BDY, whereas a higher fecal output was observed for those dogs fed the BDY+DDGS treatment.…”
Section: Food Intake and Fecal Characteristicscontrasting
confidence: 83%
“…This shift in nutrient composition could improve nutrient digestibility and consumer perception of distillers dried grains, allowing for their increased use in pet food. Corn fermented protein has previously been compared with SBM and CGM in both dogs and cats (Kilburn-Kappeler et al, 2022;Kilburn-Kappeler and Aldrich, 2023;Smith and Aldrich, 2023). However, CFP has not been compared with traditional distillers dried grains when fed to dogs or cats.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, new sources of plant-based protein have been considered, such as distillers dried grains with solublesor corn-fermented proteins. These protein sources are highly nutritional, and they also proved to be palatable to cats, possibly due to the presence of yeast, known for its high presence of nucleotides appreciated by cats [118].…”
Section: Protein Sourcesmentioning
confidence: 99%
“…According to a recent survey (6), only 19% of respondents would continue to buy pet foods with conventional protein sources, while 54% of respondents were interested in foods containing by-products, although 66% of them were not familiar with the term "by-products. " Increasing interest has emerged in alternative protein sources from terrestrial (7)(8)(9)(10) and aquatic (11,12) origin to replace conventional terrestrial ones due to their high nutritive value and lower environmental impact (13,14). Under a circular economy perspective, the utilization of by-products from aquatic sources offers additional advantages as it contributes to the reduction of waste and food-feed competition, and to a greater economic and environmental efficiency (15,16).…”
Section: Introductionmentioning
confidence: 99%